Development in wastewater treatment research and processes : bioelectrochemical systems for wastewater management - Shah, Maulin P.; Rodriguez-Couto, Susana; Kumar, Ashok (Professor of microbial biotechnology); Daverey, Achlesh (Elsevier, 2022)
Industrial wastewater contains a large variety of compounds, such as hazardous organic pollutants, heavy metals, salts and nutrients, which makes its treatment challenging. On the other hand, the sewage treatment with existing technologies is not cost-effective due to high energy demand and contributes to greenhouse gas emission. Thus, the use of conventional water treatment methods is neither sustainable nor always effective. In this sense, BESs has emerged as a promising technology to treat complex industrial wastewater with a sustainable manner. Development in Wastewater Treatment Research and Processes: Bioelectrochemical Systems for Wastewater Management analyses and discusses the potential of microbial and electrochemical based hybrid processes for the treatment of complex industrial wastewater along with the recovery of valuable compounds and water reutilization. The most significant advantages of BES are high effectiveness, low toxicity, gentle operation conditions, environmentally friendly treatment without sludge accumulation and energy conservation. Bioelectrochemical systems (BES) are emerging as an exciting platform to convert chemical energy of organic wastes into electricity or hydrogen or value-added chemical commodities. In addition, recent and future trends in BES are highlighted.